2010
DOI: 10.1259/dmfr/25151578
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of magnetic resonance imaging for detecting osseous abnormalities of the temporomandibular joint and its correlation with cone beam computed tomography

Abstract: Although high specificity (84-98%) was obtained with MRI, this modality showed relatively low sensitivity (30-82%) for detecting osseous abnormalities of the TMJ. The value of MRI for the detection of TMJ osseous abnormalities is considered to be limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 23 publications
5
54
1
7
Order By: Relevance
“…18,33,34 The diagnostic efficacy of CBCT for detecting these osseous changes is superior to that of panoramic radiography, linear tomography and MRI. 19,35 Bony changes associated with OA include irregular and possibly thickened cortical outlines, erosions, osteophyte formation, and subchondral 'cyst' formation. 9,36,37 Other changes include narrowing of the joint space and other signs of osseous remodelling such as flattening of the articular surfaces and subchondral sclerosis.…”
Section: Osteoarthritismentioning
confidence: 99%
“…18,33,34 The diagnostic efficacy of CBCT for detecting these osseous changes is superior to that of panoramic radiography, linear tomography and MRI. 19,35 Bony changes associated with OA include irregular and possibly thickened cortical outlines, erosions, osteophyte formation, and subchondral 'cyst' formation. 9,36,37 Other changes include narrowing of the joint space and other signs of osseous remodelling such as flattening of the articular surfaces and subchondral sclerosis.…”
Section: Osteoarthritismentioning
confidence: 99%
“…This variation may be influenced by issues associated with the classification of the disorders evaluated and by characteristics of the observer [23][24][25][26][27][28][29]34,35 . However, it is known that other factors may also affect MRI quality and consequently interfere with reproducibility, such as magnetic field strength 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though MRI is considered appropriate to examine the TMJ, research has reported discrepancies between MRI-based and clinical diagnoses 1,[16][17][18][19][20][21][22] . Additionally, studies that evaluated the reproducibility of this method indicate the occurrence of conflicting values [23][24][25][26][27][28][29] . This may be due to two main factors: image quality and observer skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Res. 5(5), 695-703 696 MRI has great advantages over the previous techniques in its ability to illustrate the soft tissue changes of the TMJ besides the detection of the osseous abnormalities (Alkhader et al, 2010). Thus, the aim of this study is to evaluate the TMJ abnormalities in RA patients using MRI.…”
Section: Issn: 2320-5407mentioning
confidence: 99%